Enhancing transparency through open government data: the case of data portals and their features and capabilities - Lněnička, Martin; Máchová, Renáta; Volejníková, Jolana; Linhartová, Veronika; Knězáčková, Radka; Hub, Miloslav (Emerald Group Publishing Limited, 2021)
Purpose The purpose of this paper was to draw on evidence from computer-mediated transparency and examine the argument that open government data and national data infrastructures represented by open data portals can help in enhancing transparency by providing various relevant features and capabilities for stakeholders' interactions. Design/methodology/approach The developed methodology consisted of a two-step strategy to investigate research questions. First, a web content analysis was conducted to identify the most common features and capabilities provided by existing national open data portals. The second step involved performing the Delphi process by surveying domain experts to measure the diversity of their opinions on this topic. Findings Identified features and capabilities were classified into categories and ranked according to their importance. By formalizing these feature-related transparency mechanisms through which stakeholders work with data sets we provided recommendations on how to incorporate them into designing and developing open data portals. Social implications The creation of appropriate open data portals aims to fulfil the principles of open government and enables stakeholders to effectively engage in the policy and decision-making processes. Originality/value By analyzing existing national open data portals and validating the feature-related transparency mechanisms, this paper fills this gap in existing literature on designing and developing open data portals for transparency efforts.
Zvyšování transparentnosti s využitím open government data: případ datových portálů a jejich funkcí a schopností
Keywords: transparency; content analysis; Delphi method; open government data; open data portals; features and capabilities; transparentnost; analýza obsahu; Delphi metoda; open government data; open data portály; funkce a schopnosti